TRANSPORTATION VERSUS AIR POLLUTION: THE CASE OF LIGHT RAIL IN PHOENIX ARIZONA/USA - Meneguzzi, Nelci Lurdes Gayeski; Dobler, Guilherme Hammastron; Tonel, Rodrigo; Ehmke, Diego Paes; Cenci, Daniel (Salão do Conhecimento, 2017)
Interdisciplinary theme among the areas of law and social sciences.